2013
DOI: 10.1371/journal.pone.0081223
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal Internal Transcribed Spacer of Prototheca wickerhamii Has Characteristic Structure Useful for Identification and Genotyping

Abstract: Prototheca species are achlorophyllous algae ubiquitous in nature and known to cause localized and systemic infection both in humans and animals. Although identification of the Prototheca species in clinical specimens is a challenge, there are an increasing number of cases in which molecular techniques have successfully been used for diagnosis of protothecosis. In this study, we characterized nuclear ribosomal DNA (rDNA) of a strain of Prototheca (FL11-0001) isolated from a dermatitis patient in Japan for its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…S1, ITS, lane 3) was shown to be smaller than that of P. wickerhamii (Fig. S1, ITS, lanes 1 and 2), confirming results of the previous study (Hirose et al, 2013). In addition, the SSU rDNA of IFM 53848 T was demonstrated to be about 3.6 kb long (Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…S1, ITS, lane 3) was shown to be smaller than that of P. wickerhamii (Fig. S1, ITS, lanes 1 and 2), confirming results of the previous study (Hirose et al, 2013). In addition, the SSU rDNA of IFM 53848 T was demonstrated to be about 3.6 kb long (Fig.…”
Section: Resultssupporting
confidence: 89%
“…As it was previously shown that PCR analysis of the rRNA gene is useful for identification of species of the genus Prototheca (Hirose et al, 2013), we amplified the SSU rDNA, the ITS and the D1/D2 region of the LSU rDNA of IFM 53848 T and various other strains of species of the genus Prototheca for comparison (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The case was recorded in a Japanese female patient, and was discussed as an interesting case during one of the regional meetings of the Japanese Dermatological Association (JDA) in 2011 . In 2013, we characterized the nuclear rDNA of the strain isolated from the patient and identified it to be Prototheca wickerhamii genotype 2 . Also, a review article published in 2014 included this patient as case 7 in its table .…”
Section: Introductionmentioning
confidence: 99%
“…2 In 2013, we characterized the nuclear rDNA of the strain isolated from the patient and identified it to be Prototheca wickerhamii genotype 2. 3 Also, a review article published in 2014 included this patient as case 7 in its table 1. 4 During the working group symposium of the 19th International Society for Human and Animal Mycology (ISHAM) Congress in 2015, Todd et al 5 listed this case in their presentation.…”
Section: Introductionmentioning
confidence: 99%